The Effectiveness, User Perceptions and Innovation in Implementing the Customs Service System at International Airports: Efektivitas, Persepsi Pengguna dan Inovasi dalam Penerapan Sistem Layanan Kepabeanan di Bandara Internasional - Kurniawan, Adi; Maradona, Agus Fredy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Directorate General of Customs and Excise (DJBC) plays a pivotal role in supervising the flow of goods through Indonesia's international airports. Specific Background: Efficient customs services are essential for national security, trade facilitation, and enhancing the international image of airports. Knowledge Gap: Despite DJBC’s strategic role, limited research has explored the effectiveness of customs officers’ performance and public perceptions at international terminals. Aims: This study aims to evaluate the effectiveness of DJBC officers in delivering services and to assess user perceptions as a basis for improving service quality and airport image reconstruction. Results: Utilizing a descriptive qualitative approach, data were gathered through observations and in-depth interviews with 11 respondents—five customs officers and six service users. The findings indicate that DJBC consistently executes its duties across planning, implementation, and reporting stages. However, user perceptions vary significantly, particularly regarding access to regulation updates, officer responsiveness, import duty transparency, and inter-agency coordination. Novelty: This study provides a grounded analysis of both institutional performance and user experiences at international arrival terminals, highlighting gaps in policy communication and coordination. Implications: The findings underscore the need for synchronized regulatory frameworks and public outreach initiatives to enhance policy clarity and service delivery at international airports. Highlights: Evaluates DJBC officers’ service effectiveness at international terminals. Highlights varied passenger perceptions and regulatory communication gaps. Recommends policy alignment and public outreach for service improvement. Keywords: Duty Tariffs, Effectiveness, International Airport, User Perception, Public Service